2013
DOI: 10.5489/cuaj.606
|View full text |Cite
|
Sign up to set email alerts
|

Clear cell myomelanocytic tumour: minimally invasive treatment of a rare bladder tumour

Abstract: Clear cell myomelanocytic tumours are extremely rare neoplastic growths considered to be members of the family of perivascular epithelioid cell tumours (PEComas), which have in common the coexpression of melanocytic and smooth muscle immunohistochemical markers. These tumours are known to be ubiquitous with uncertain tumour biology and to have unpredictable clinical behaviour. They have been reported in the genitourinary tract, including the kidney and prostate. There are only 3 reported cases of clear cell my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Again histology showed PEComa. The patient was clinically free of disease 3 months after surgery (9).…”
Section: Discussionmentioning
confidence: 99%
“…Again histology showed PEComa. The patient was clinically free of disease 3 months after surgery (9).…”
Section: Discussionmentioning
confidence: 99%
“…A few patients were managed with TURBT alone and did not require further surgical intervention 7 8 11. There are several reports of PEComas of the bladder treated successfully with partial cystectomy 7 10 12 13 17 18 21. In two other cases, patients underwent radical cystectomy for metastatic tumours exhibiting aggressive clinical behaviour 9 14.…”
Section: Discussionmentioning
confidence: 99%
“…In two other cases, patients underwent radical cystectomy for metastatic tumours exhibiting aggressive clinical behaviour 9 14. Pianezza et al 21 described in detail a laparoscopic partial cystectomy for resection of a CCMMT. While the use of robotics for the management of common bladder lesions such as urothelial carcinoma has become routine, a robotic approach to partial cystectomy for the treatment of PEComa of the bladder has not been described in prior literature.…”
Section: Discussionmentioning
confidence: 99%
“…Another case of primary PEComa of the bladder has been described with the patient being alive 4 years after partial cystectomy and adjuvant interferon-␣ immunotherapy [8] . In 2008, Pianezza et al [9] reported the 4th documented case of bladder PEComa in an 24-year-old woman with chronic pelvic pain who underwent laparoscopic partial cystectomy of a bladder PEComa. More recently, Sukov et al [10] reported 3 cases of bladder PEComa in 2 men in their 4th decade and 1 woman in her 3rd decade.…”
Section: Discussionmentioning
confidence: 99%